Ralstonia solanacearum and R. pseudosolanacearum on Eucalyptus: Opportunists or Primary Pathogens? - Coutinho, Teresa A.; Wingfield, Michael J. (Frontiers in Plant Science, 2017)
Ralstonia solanacearum and R. pseudosolanacearum are well known primary pathogens of herbaceous crops. Reports of wilt caused by these pathogens in tree species are limited other than on Eucalyptus species. Despite the widespread occurrence of so-called bacterial wilt on eucalypts in tropical and sub-tropical parts of Africa, Asia, and the Americas, there remain many contradictions relating to the disease. Our field observations over many years in most regions where the disease occurs on Eucalyptus show that it is always associated with trees that have been subjected to severe stress. The disease is typically diagnosed by immersing cut stems in water and observing bacterial streaming, but the identity of the bacteria within this suspension is seldom considered. To add to the confusion, pathogenicity tests on susceptible species or clones are rarely successful. When they do work, they are on small plants in greenhouse trials. It has become all to easy to attribute Eucalyptus death exclusively to Ralstonia infection. Our data strongly suggest that Ralstonia species and probably other bacteria are latent colonists commonly occurring in healthy and particularly clonally propagated eucalypts. The onset of stress factors provide the bacteria with an opportunity to develop. We believe that the resulting stress weakens the defense systems of the trees allowing Ralstonia and bacterial endophytes to proliferate. Overall our research suggests that R. solanacearum and R. pseudosolanacearum are not primary pathogens of Eucalyptus. Short of clear evidence that they are primary pathogens of Eucalyptus it is inappropriate to attribute this disease solely to infection by Ralstonia species.